The Influence of the Connected Mathematics Project Model on Mathematics Learning on Students’ Mathematics Learning on Students’ Mathematical Reasoning Abilities at SMAN 2 Rumbio Jaya - Nurhaleni Nurhaleni; Kasman Ediputra; Astuti Astuti (Edumaspul: Jurnal Pendidikan, 2023)
This research was motivated by the problem of low mathematical reasoning ability of students in mathematics learning in grade XI SMAN 2 Rumbio Jaya. One solution to overcome this problem is to use the connected mathematics project (CMP) learning model. The purpose of this study was to improve the mathematical reasoning ability of high school students. This type of research is quasi-experimental research or pseudo-experiments involving two classes that are given different treatments, namely the experimental class and the control class. The research subjects consisted of class XI where class XI IPS1 was an experimental class with a total of 19 people and class XI IPS2 in the form of a control class with a total of 21 people. The sample technique uses simple random sampling. Before being given experimental class treatment and control class is first given a test, namely pretest, and after being given experimental class treatment and control class given posttest test. The results of this study, students' mathematical reasoning ability in the control class was found to be on average in the control class of 76.19 while in the experimental class it was found to be an average of 83.00. So that the Connected Mathematics Project model has a significant effect on the mathematical reasoning ability of grade XI students of SMA Negeri 2 Rumbio Jaya. This is evidenced by an independent t-test, where the sig value is 0.000 < 0.05.